Study on Bridge Structural Health Monitoring System Based on BIM And GIS - Wang, Yiran (Transactions on Engineering and Technology Research, 2024)
In the context of rapid urbanization, the importance of bridge construction has become increasingly prominent, but problems such as bridge aging and environmental impact have also brought security risks. To deal with these problems, it is very important to establish an efficient and accurate bridge monitoring system. Firstly, this paper analyzes the research status of bridge health monitoring system and points out that there are some problems in the current system, such as weak analysis system, imperfect data storage and analysis. Then, the basic principle of Building Information Modeling (BIM)and Geographic Information System (GIS) technology and its application advantages in bridge monitoring are introduced in detail. BIM technology provides detailed building information through 3 Dimensions(3D) models to improve the accuracy of monitoring; GIS integrates geospatial data to realize data visualization and spatial analysis. After that, the paper discusses the specific application of BIM and GIS integration, including 3D model display, perception and monitoring, assessment and early warning, intelligent inspection and other functions. Through the deep integration of BIM-GIS technology, the system can monitor the bridge in real time, find and warn potential problems, and improve management efficiency and safety. Finally, the paper summarizes the research results, points out the significant advantages of the integration of BIM and GIS technology in bridge health monitoring, and looks forward to the future development trend.